ChatGPT in healthcare education: a double-edged sword of trends, challenges, and opportunities - Michael Agyemang Adarkwah; Samuel Anokye Badu; Evans Appiah Osei; Enoch Adu-Gyamfi; Jonathan Odame; Käthe Schneider (Discover Education)
Abstract The advancement of artificial intelligence (AI) tools has revolutionized teaching and learning, particularly in healthcare education, where they enhance pedagogy, foster immersive learning, and support healthcare provision. However, their use in healthcare education is contentious, warranting careful examination, especially regarding Generative AI (GenAI) tools like ChatGPT. This scoping review aims to explore the impact of ChatGPT on healthcare education and identify future research directions. The scoping review, conducted in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statement, utilized search terms such as “ChatGPT,” “GPT,” “natural language processing,” “large language models,” and “health education”. The review followed the five-stage framework outlined for organization and analysis. The search encompassed Web of Science (WOS) (n = 100), PubMed (n = 100), CINAHL (n = 21), SCOPUS (n = 4), Science Direct (n = 25), and Google Scholar (n = 150). Initially, 400 papers were retrieved from these search engines, which were then reviewed and narrowed down to 33 papers for final analysis. This review investigated the trends, challenges, and  opportunities of ChatGPT in healthcare education. The findings suggest that GenAI tools such as ChatGPT can significantly enhance teaching, learning, and research in healthcare education. Developed countries, particularly the United States and China, which are leaders in AI investment and research, lead research on ChatGPT's applications in healthcare education, with limited studies conducted in the African region. Additionally, barriers remain that could lead to ethical and legal issues, particularly exacerbating inequalities in developing countries. Further research is needed to promote better GenAI practices in healthcare educational settings, especially for individuals in these regions.